63Fe–63Mn: A Possible Strong Urca Pair and Its Potential Astrophysical Impact - Hao Huang; Kuoang Li; Zhong Liu; Xiaodong Tang; Peng Shuai; Zach Meisel (The Astrophysical Journal)
The cooling strength of the Urca pair, ^63 Fe– ^63 Mn, exhibits an extensive range of variation due to the uncertainty in the spin parity of the ground state of ^63 Fe. To investigate the cooling effect of this Urca pair on the thermal evolution of neutron star crusts, we performed simulations on neutron star structure and evolution under various spin-parity assignment scenarios. When adopting recently evaluated nuclear data, ^63 Fe– ^63 Mn emerges as one of the strongest Urca pairs. In the case of MAXI J0556-332, ^63 Fe– ^63 Mn is the only pair above the shallow heating layer, significantly impacting the cooling curve and the superburst ignition. Moreover, the constraint on the past nucleosynthesis reduced to one-quarter of its original value, falling within three decades, which enables the validation of nuclear reaction theories in the outer layers of neutron stars. Our results highlight the need for more precise measurements of the β ^− decay of ^63 Mn to better determine the Urca cooling effect of the ^63 Fe– ^63 Mn pair in accreted neutron star crusts.